Estudo da remoção de Ba2+, Ni2+, Cd2+, Cu3+, Cr3+, Sr2+, Zn2+ por eletrocoagulação em água associada à produção de petróleo - Souza, Kátia Regina (2012)
Among the waste generated in the petrochemical industry water associated with oil production is the most important. It is considered one of the great challenges due to the presence of considered toxic chemicals present in this composition. The presence of these substances difficult to reuse the water associated with the enhanced recovery processes, so that prior to their reuse or disposal, treatment is necessary. This paper aimed to study the removal efficiency of chemical species: Ba2+, Ni2+, Cd2+, Cu2+, Cr3+, Sr2+ and Zn2+, present in the composition of the water associated with oil production by electrocoagulation. The evaluation of removal of these chemical species was performed by laboratory tests using electrochemical batch reactors and continuous flow. Initial tests were performed with electrocoagulation of synthetic wastewater in batch reactor using iron electrode. Results of removal of Zn2+ and Ni2+ were 78 % and 59 % respectively. While the percentage of removed Ba2+ was 19 % by 30 minutes of treatment and by applying current of 1.10 A. The tests were performed on effluent batch reactor applying the electrochemical technique with stainless steel electrodes 304, the objective was to remove part of the dispersed oil and also of organic compounds in the effluent. Under the experimental conditions used, the maximum result was obtained TOG was 60 % and TOC was approximately 50 % compared to the initial concentration. In the experiments carried out in continuous reactor, with effluent semisynthetic, have been used electrodes of iron and aluminum and the results were 100 % removal of Cd2+, Cu2+, Cr3+ and Zn2+ and 77 % of Sr2+. These percentages were only attainable through the use of the iron electrode. However, when the electrode was replaced by aluminum, there was a reduction in the percentage of removal to 65 %, using the same flow rate and current. Therefore according to the results obtained using the iron electrode was more effective in removing these metals and the conditions of lower current and lower flow rate was satisfactory, as observed in the experimental design adopted